Study guides

☆☆

Q: What is the answer to 8-1 plus 3x2 plus 6?

Write your answer...

Submit

Still have questions?

Related questions

3x2 + 36x + 81 = 3(x2 + 13x + 27)

It is: (3x+27)(x+3)

3x2=6+38=44

(3X + 9) (X + 9)

All terms include 3x2. So we can factor the expression as :- 3x6 + 54x4 + 243x2 = 3x2(x4 + 18x2 + 81) And (x4 + 18x2 + 81) = (x2 + 9)2 Putting the two parts together gives, 3x2(x2 + 9)2.

-3x2 + 16x + 12 = -3x2 + 18x - 2x + 12 = -3x*(x - 6) - 2(x - 6) = -(3x + 2)*(x - 6)

3x2 + 36x + 81 = 3(x2 + 12x + 27) = 3(x + 3)(x + 9), which are its prime factors; or, if you prefer, 3x2 + 36x + 81 = (3x + 9)(x + 9), which is also accurate. You may easily verify these results by multiplying back.

(2x3)+(3x5)-(3x2)= 2x3=6 3x5=15 3x2=6 So..... 6x25-6= 6x25=150 150+6=156

3x2+7-6 = (3x-2)(x+3) when factored

6

(3x + 1)(x + 6)

no 3x2=6 then 4x-15= -60 so 6 added with - 60 = -54

People also asked